2015
DOI: 10.1007/s00432-015-2061-8
|View full text |Cite
|
Sign up to set email alerts
|

Race and sex disparities in long-term survival of oral and oropharyngeal cancer in the United States

Abstract: Overall and disease-specific survival is poor for oral and oropharyngeal cancer patients, and Black men fare worst. This illustrates the need for long-term cancer survival plans incorporating disparity effects in overall cancer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
95
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 49 publications
13
95
1
1
Order By: Relevance
“…Supporting these recommendations, we found that patients receiving surgery have a statistically significantly better survival compared with those receiving CRT. We also show a significant disparity in oral cavity SCC survival between non‐Hispanic white patients and non‐Hispanic black patients, which corroborates the findings of previous studies . This difference is partially explained by differences between non‐Hispanic black patients and non‐Hispanic white patients in actual treatment received; non‐Hispanic black patients were 11% less likely than non‐Hispanic white patients to receive surgery when controlling for potential confounders.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Supporting these recommendations, we found that patients receiving surgery have a statistically significantly better survival compared with those receiving CRT. We also show a significant disparity in oral cavity SCC survival between non‐Hispanic white patients and non‐Hispanic black patients, which corroborates the findings of previous studies . This difference is partially explained by differences between non‐Hispanic black patients and non‐Hispanic white patients in actual treatment received; non‐Hispanic black patients were 11% less likely than non‐Hispanic white patients to receive surgery when controlling for potential confounders.…”
Section: Discussionsupporting
confidence: 90%
“…Squamous cell carcinomas (SCCs) of the head and neck are a relatively heterogeneous group of malignancies with multiple subsites that can be treated with either definitive surgery or radiation, with or without chemotherapy. Non‐Hispanic black patients, when compared with non‐Hispanic white patients, present with more advanced disease, are less likely to receive definitive cancer treatment, and experience poorer survival . The non‐Hispanic black patients are less likely to have up‐front surgery recommended for oral cavity and oropharyngeal cancers and are less likely to actually receive surgery for oropharyngeal cancers …”
Section: Introductionmentioning
confidence: 99%
“…Previous literature showing black race, lack of social support (especially marriage), lack of insurance, and low socioeconomic status negatively impact HNSCC survival were confirmed among younger patients in this study. However, these effects differed among the elderly.…”
Section: Discussionsupporting
confidence: 85%
“…A Fine‐Gray multivariate competing risk model was developed for each age cohort to identify variables associated with cancer‐specific survival . Covariates were selected for inclusion in the model based on previous literature identifying a correlation with HNSCC mortality . All collected data as listed above were eligible for inclusion in the model and detailed definitions are available from SEER .…”
Section: Methodsmentioning
confidence: 99%
“…There are known racial disparities in both the incidence and outcomes for patients who develop HNCA. African Americans in the United States are more likely to present with late stage disease and to have worse survival . Similarly, American Indians with HNCA are more likely to present with late stage disease, less likely to receive surgery for cancer of the oral cavity, and more likely to die from their disease than their white counterparts in the United States …”
Section: Introductionmentioning
confidence: 99%